Modulation of working-memory maintenance by directed attention. - Lepsien, J; Thornton, I; Nobre, A (2011)
Many current models of working memory (WM) emphasize a close relationship between WM and attention. Recently it was demonstrated that attention can be dynamically and voluntarily oriented to items held in WM, and it was suggested that directed attention can modulate the maintenance of specific WM representations. Here we used event-related functional magnetic resonance imaging to test the effects of orienting attention to a category of stimuli when participants maintained a variable number of faces and scenes in WM. Retro-cues that indicated the relevant stimulus type for the subsequent WM test modulated maintenance-related activity in extrastriate areas preferentially responsive to face or scene stimuli - fusiform and parahippocampal gyri respectively - in a categorical way. After the retro-cue, the activity level in these areas was larger for the cued category in a load-independent way, suggesting the modulation may also reflect anticipation of the probe stimulus. Activity in associative parietal and prefrontal cortices was also modulated by retro-cues, and additionally co-varied with the number of stimuli of the relevant stimulus category that was being maintained. The findings suggest that these associative areas participate in maintaining the relevant memoranda in a flexible and goal-directed way to guide future behaviour.